Destilasi Minyak Atsiri di Kawasan Hutan Giring, Paliyan, Gunungkidul - Septiono Eko Bawono; Rosalia Widhiastuti SL Rosa; Anwarudin Hisyam; Tri Putro Pamungkas (Jurnal Ilmiah Padma Sri Kreshna, 2025)
Abstract — The production of citronella in the Giring forest area involves Women’s Farmer Groups (KWT) and Forest Farmer Groups (KTH), who cultivate the plant in large quantities. Through an experimental approach, a simple essential oil distillation unit was constructed, followed by a production trial. The trial resulted in the extraction of crude essential oil with economic value. This activity has provided direct benefits to KWT and KTH by enhancing their knowledge and skills in processing citronella into essential oil, while also creating new opportunities to increase income and improve the local community’s economy. Keywords — production of citronella, Women’s Farmer Groups (KWT), Forest Farmer Groups (KTH), crude essential oil, community’s economy.